GERBANG OTOMATIS DENGAN PENGUKURAN SENSOR MLX90614 BERBASIS ARDUINO SEBAGAI ALAT PENCEGAHAN PENULARAN AWAL COVID-19 - Sulis Sutiono; Magdalena Simanjuntak; Nurhayati (Kampus Akademik Publiser, 2024)
Maintaining health is very important for life, especially during the current covid-19 pandemic. One of the protocols imposed by the government for people who are active in public spaces or open facilities is to check their body temperature. In this study, a design for preventing the initial transmission of covid-19 was made with an arduino-based body temperature which has an automatic door if the body temperature is above 37.30 the door will not open and if it is below normal the door will also not open. This tool for preventing the initial transmission of covid-19 uses the MLX90614 sensor to measure temperature in units of celsius (0c). Body temperature data is also displayed on the 16x2 (cm) lcd on the device. The test results of measuring body temperature are compared with a thermo gun. This automatic gate with arduino-based mlx90614 sensor measurement as a prevention tool for early covid-19 transmission is expected to be installed in public places that require inspections of people who will be active in the room, the operator can stand at the control desk so that there is no direct contact with the public .